Visual efficient chloride ion removal adsorption material as well as preparation method and application thereof

By preparing porous hollow glass microspheres loaded with magnetic iron oxide nanoparticles, the problem of balancing efficiency and cost in traditional chloride ion treatment technology has been solved, achieving efficient and visualized chloride ion removal and recovery.

CN121669200APending Publication Date: 2026-03-17NANJING TECH UNIV +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202511321068.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-09-16
Publication Date
2026-03-17

AI Technical Summary

Technical Problem

Existing chloride ion treatment technologies struggle to balance efficiency, cost, and operational difficulty. Traditional adsorption materials suffer from limited adsorption capacity, insufficient stability, poor specificity, and low operational visibility during chloride ion removal.

Method used

Hollow glass microspheres were used as a carrier to prepare porous hollow glass microspheres by spray laser-induced micro-explosion method. The microspheres were then modified by sol-gel method and low-temperature plasma bombardment technology to load magnetic iron oxide nanoparticles, forming a porous adsorbent material with high specific surface area, which enhances the adsorption selectivity and visual recovery capability of chloride ions.

Benefits of technology

It achieves efficient and visualized chloride ion adsorption and recovery, with high adsorption capacity, low cost, simple operation, and suitability for acidic water quality. It can also be reused.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121669200A_ABST
    Figure CN121669200A_ABST
Patent Text Reader

Abstract

The invention discloses a visual efficient chloride ion removal adsorbing material and a preparation method and application thereof.The adsorbing material is prepared by the steps that hollow glass microspheres serve as a carrier, and hollow glass porous particles are synthesized from a mixture of hollow glass microsphere powder and a pore forming agent through a sol-gel method; the preparation method comprises the following steps: modifying the surface of a porous adsorption material through a low-temperature plasma bombardment technology to enhance the adsorption performance on chloride ions, and loading magnetic iron oxide nanoparticles on the porous adsorption material to prepare the chloride ion adsorption material; the adsorption material has the characteristic of environmental friendliness, not only can efficiently adsorb chloride ions in a water body, but also can realize the visualization of the adsorption process through the density difference before and after adsorption, has the characteristics of repeated use and easiness in regeneration, and has relatively high market application prospect and economic value.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention provides a visually efficient chloride ion removal adsorption material and its preparation method, belonging to the field of water pollution control. Background Technology

[0002] Water, as a fundamental resource for human survival and development, faces severe challenges to its sustainable use brought about by the accelerated pace of industrialization and urbanization. According to statistics from the United Nations Environment Programme, approximately 80% of industrial wastewater worldwide is discharged directly without effective treatment, and health crises caused by water pollution result in millions of deaths annually. Water pollution control has become an urgent issue in the global environmental science field.

[0003] Currently, the main technologies for efficient removal of chloride ions from wastewater include flue gas evaporation, evaporation concentration, ion exchange, electrolysis, extraction, and adsorption. The principles, advantages, and limitations of each technology are analyzed below:

[0004] (1) Flue gas evaporation technology

[0005] This technology is widely used in the field of desulfurization wastewater treatment. Its core process involves pre-treating wastewater in a three-stage pumping unit, then pumping it via a high-pressure pump to atomizing nozzles in the flue gas duct before the dust collector for atomization and evaporation. Its advantages include a simple process flow, low operating and maintenance costs, and the ability to achieve "zero discharge" of wastewater. However, this technology has drawbacks, including the risk of nozzle clogging, flue gas ash accumulation, and the adverse effects of solid salts mixing with fly ash on the comprehensive utilization of fly ash. Furthermore, this technology relies on the calorific value of high-temperature flue gas, increasing coal consumption for power generation and limiting its application in non-coal-fired power plants.

[0006] (2) Evaporation and Concentration Technology

[0007] This technology utilizes waste heat from power plants to evaporate and concentrate wastewater, recycles the condensed steam, and centrally treats the concentrated liquid crystallized salt. Its advantage lies in achieving resource utilization of wastewater and salt; however, it is costly, energy-intensive, complex to operate, and requires a large area, limiting its widespread adoption in small and medium-sized wastewater treatment facilities.

[0008] (3) Ion exchange technology

[0009] The efficient removal of chloride ions is achieved by selectively exchanging ion exchange resins with wastewater. This technology is mature, the materials are regenerable, and the removal efficiency is high without introducing new impurities. However, its resistance to interference is weak, its exchange capacity is limited, and the pollutants in the regenerated solution require further treatment, increasing the system complexity.

[0010] (4) Electrolysis process

[0011] Electrolysis removes chloride ions through electrochemical reactions, but it has limitations such as high energy consumption, high operating costs, and safety hazards. Further optimization of process parameters is needed to improve economic efficiency.

[0012] (5) Extraction and Adsorption Methods

[0013] Extraction methods suffer from reduced efficiency due to their complex procedures and tendency to lead to chloride ion enrichment; adsorption methods face challenges such as insufficient stability of adsorbent materials, poor specific adsorption capacity, difficulty in recovery, and low level of operational visualization. These limitations indicate that developing novel, highly efficient adsorbent materials that specifically adsorb chloride ions and offer visualized recovery capabilities has become a key technological requirement in the wastewater treatment field.

[0014] Patent (CN201510808023.X) discloses a method for preparing a chloride ion adsorbent. The method involves mixing Fe2(SO4)3, FeCl2, and NiCl2, then adding an aqueous sodium hydroxide solution to adjust the pH. After stirring and drying, Ni-doped nano-iron oxide magnetic powder is obtained, followed by a sol-gel method to obtain magnetic zirconium hydroxide. Its advantages include high adsorption capacity and the ability to recover the adsorbent using magnetic properties. However, there are also significant areas for improvement. Accurately determining the adsorption endpoint is difficult. The suitable pH range for nano-magnetic zirconium hydroxide is 1-2, which is strongly acidic water, making the suitable range quite demanding. Furthermore, the influence of anion interference on the adsorption of chloride ions by nano-magnetic zirconium hydroxide is still unclear, posing considerable challenges in practical wastewater treatment. Summary of the Invention

[0015] The purpose of this invention is to address the current difficulty in balancing efficiency, cost, and operational complexity in chloride ion treatment environments by proposing an effective solution. This solution is achieved by developing a visually efficient chloride ion removal adsorption material and its preparation method.

[0016] The objective of this invention can be achieved through the following technical solution: The adsorbent material uses hollow glass microspheres as a carrier, leveraging their low cost, environmental friendliness, and chemical stability to achieve both economic efficiency and safety. The hollow glass microspheres are prepared by a spray laser-induced micro-explosion method, resulting in more uniform wall thickness compared to traditional spray drying; and higher yield and efficiency compared to the laser-induced method. In the preparation of the hollow glass microsphere powder, trimethylaminoborane serves as a high-performance amino-containing boron source. Boron in the hollow glass microspheres provides thermal stability, high mechanical strength, and good optical properties. Furthermore, the synthesized hollow glass microspheres are loaded with a certain amount of amino groups, enhancing their adsorption performance for chloride ions. Tetraethyl orthosilicate, with its mild reaction conditions, chemical resistance, and high solubility, is a common material used in sol-gel methods in materials science. Tetraethyl orthosilicate and NaOH are mixed in deionized water and stirred. Tetramethylguanidine (TVC) reacts in an alkaline environment with NaOH to form Si(OH)₄. Si(OH)₄ is highly unstable and undergoes continuous condensation reactions, gradually forming SiO₂ gel at a lower cost, thus creating a stable sol system. Tetramethylguanidine-sodium bicarbonate (TMD) is an excellent pore-forming agent due to its clean decomposition products, mild reaction conditions, and good water solubility and dispersibility. It exhibits resistance to agglomeration among pore-forming agents. Hollow glass microsphere powder is mixed and dissolved with TMD in water, then added to the formed sol system. After stirring for a period of time, particles are gradually formed. Upon heating, TMD begins to decompose, releasing gas. As the gas escapes from the sol system, it leaves micropores on the surface of the spherical hollow glass microspheres. Ultrasonic pulse treatment enhances the surface area of ​​these micropores, improving the loading effect of subsequent magnetic iron oxide nanoparticles. The porous hollow glass microspheres were bombarded with low-temperature plasma to further enhance their specific surface area. Due to the participation of NH3 during low-temperature plasma bombardment, amino groups were formed on the surface of the hollow glass microspheres. In water, these amino groups were protonated to form positively charged -NH4+. + Highly efficient capture of Cl through electrostatic attraction - It can enhance the resistance to Cl - The adsorption selectivity and adsorption performance are improved. Bombardment also increases the specific surface area of ​​the adsorption, enhancing its adsorption and loading effects, transforming hollow glass microspheres into porous adsorption materials with high specific surface area. Magnetic iron oxide nanoparticles were synthesized, exhibiting improved magnetism and resistance to Cl... - The high adsorption capacity is a crucial factor in enabling the adsorption material to be visualized, highly efficient, and reusable. During the synthesis of magnetic iron oxide nanoparticles, polyethylene glycol is added as a dispersant to prevent rapid aggregation. The nanoparticles are then added to a homogeneous solution of porous hollow glass microspheres to load them into the micropores of the adsorption material. After washing and drying, the desired visualized and highly efficient chloride ion removal adsorption material is obtained.

[0017] In practical applications, this adsorbent material features high efficiency, high adsorption capacity, low cost, simple operation, recyclability, and a visible adsorption process. Specific operation: The adsorbent material is placed into the water body to be treated. Initially, due to its density, the adsorbent material will float on the water. After a period of adsorption, the density increases due to the increase in adsorbed ions and other impurities. When the density exceeds that of water, it can be considered that one adsorption cycle has been completed. Magnetic iron oxide nanoparticles are then used to extract the adsorbent, and finally, the material is placed in a sodium hydroxide aqueous solution to complete the desorption process.

[0018] A visually efficient chloride ion removal adsorption material is proposed. The adsorption material uses hollow glass microspheres as a carrier. Hollow glass porous microspheres are synthesized by sol-gel method with a mixture of hollow glass microspheres and pore-forming agent. The surface of the microspheres is modified by low-temperature plasma bombardment technology. Magnetic iron oxide nanoparticles are loaded onto the porous adsorption material to prepare the chloride ion adsorption material.

[0019] A method for preparing the above-mentioned visualized and efficient chloride ion removal adsorbent material is as follows:

[0020] (1) Preparation of hollow glass microspheres by spray laser-induced micro-explosion method

[0021] Boron source, silicon source, soda ash, limestone and flux are mixed and melted in a high-temperature melting furnace. After cooling, the resulting blocky material is atomized. After atomization, droplets are collected with silicone oil and transferred to a quartz glass slide. Under the laser irradiation and micro-explosion induction of a femtosecond laser, the droplets are cooled in an air atmosphere. Finally, they are washed, dried and calcined in sequence. After calcination, they are cooled and sieved to obtain hollow glass microspheres.

[0022] (2) Preparation of porous hollow glass microspheres by sol-gel method

[0023] After cleaning the hollow glass microspheres obtained in step (1), they were mixed with deionized water and pore-forming agent powder was added and mixed evenly to obtain mixed solution A; after mixing the silanol salt with alkaline solution, mixed solution B was obtained; mixed solution A was added to mixed solution B and mixed evenly, and then treated at 150-175℃ for 1-2 hours. Finally, ultrasonic pulse treatment, solid material was extracted by vacuum filtration and static aging for 1-3 hours were performed in sequence. After aging, the microspheres were screened to obtain porous hollow glass microsphere spherical particles.

[0024] (3) Preparation of modified spherical particles by low-temperature plasma bombardment

[0025] In an Ar / NH3 mixed gas atmosphere, the porous hollow glass microsphere spherical particles obtained in step (2) were bombarded with low-temperature plasma. After the bombardment, N2 was used to cool them down. Then, they were washed and dried in sequence to obtain modified hollow glass microsphere spherical particles.

[0026] (4) Preparation of magnetic iron oxide nanoparticles and their loading by microemulsion coprecipitation method

[0027] The surfactant and oil phase solvent are mixed to form solution C; the dispersant is rapidly added to the iron salt solution to obtain solution D; solution D is slowly added to solution C and stirred to obtain microemulsion A;

[0028] To prepare solution C, slowly add ammonia solution dropwise to solution C and stir to obtain microemulsion B;

[0029] Microemulsion A and microemulsion B were mixed, stirred, centrifuged, washed, heated and dried in a tube furnace, and cooled to obtain magnetic iron oxide nanoparticles.

[0030] The modified hollow glass microspheres from step (3) were dispersed in deionized water and dispersed evenly to obtain solution E. Magnetic iron oxide nanoparticles were added to solution E and stirred with a magnetic stirrer at 50-80°C for 0.5-1 h. Alkali solution was slowly added to carry out the reaction. After the reaction was completed, the product was magnetically separated using a magnet. The supernatant was discarded, and the product was washed again until the washing liquid was neutral. The product was then dried in a tube furnace and sieved to obtain the target adsorbent material.

[0031] In the above preparation method, the conditions for step (1) are as follows:

[0032] The boron source is trimethylaminoborane, the silicon source is silicon carbide, and the co-solvent is sodium fluoroborate;

[0033] The mass ratio of the boron source, silicon source, soda ash, limestone and co-solvent is 15-20:50-60:10-20:5-10:1-10;

[0034] The melting temperature is 1400–1500℃, and the melting time is 1–2 hours.

[0035] The femtosecond laser has a wavelength of 300–360 nm, a single pulse energy of 15–25 μJ, and a repetition frequency of 0.5–1.5 kHz.

[0036] The calcination temperature is 600–800℃, and the calcination time is 1.5–2 hours.

[0037] The target particles are selected from those that pass through a 100-mesh standard sieve and are retained on a 500-mesh standard sieve.

[0038] In the above preparation method, the conditions for step (2) are as follows:

[0039] The pore-forming agent is a mixture of tetramethylguanidine and sodium bicarbonate, with a mass ratio of tetramethylguanidine to sodium bicarbonate of 1:(5-11).

[0040] The mass ratio of silanol salt to alkaline solution in the mixed solution B is 1:(0.1-0.3); the silanol salt is tetraethyl orthosilicate, and the alkaline solution is a 0.05-0.15 mol / L sodium hydroxide solution;

[0041] The mass ratio of the hollow glass microspheres, silanol salts, and pore-forming agent powder is (10-20):(50-80):(6-15);

[0042] The ultrasonic pulse processing time is 1 to 3 minutes, and a pulse mode of working for 1 second and pausing for 2 to 3 seconds is adopted.

[0043] The target particles to be screened are the target products that have passed through a 20-mesh standard sieve and are retained on a 30-mesh standard sieve.

[0044] In the above preparation method, the conditions for step (3) are as follows:

[0045] The conditions for low-temperature plasma bombardment are: power set to 300-700W, RF generator power set to 20W, pressure maintained in a vacuum environment of 0.4-1.6Pa, temperature 100-150℃, and bombardment time 15-20 minutes.

[0046] The drying temperature is 60-80℃, and the drying time is 6-8 hours;

[0047] The Ar / NH3 mixed gas contains 16-20% Ar by volume.

[0048] In the above preparation method, the conditions for step (4) are as follows:

[0049] The surfactant is hexadecyltrimethylammonium bromide, the oil phase solvent is cyclohexane, the iron salt is FeCl3·6H2O, and the dispersant is polyethylene glycol;

[0050] The mass ratio of surfactant to oil phase solvent in solution C is 1:(5.67~19);

[0051] The concentration of the iron salt solution in solution D is 0.1–0.3 mol / L, and the mass ratio of iron salt to dispersant is 1:(2–3).

[0052] In the preparation process of the microemulsion A, the mass ratio of solution C to solution D is 1:(0.2~0.5).

[0053] In microemulsion B, the mass ratio of solution C to ammonia solution is 1:(1-10), and the mass concentration of ammonia solution is 25-30%.

[0054] The mass ratio of microemulsion A to microemulsion B is 1:(1~1.2);

[0055] The conditions for heating and drying in a tube furnace are: the atmosphere is a mixture of oxygen and nitrogen, the oxygen volume content is 1-10%, the heating temperature is set at 200-300℃, and the heating time is 2-3 hours.

[0056] The drying conditions in the tube furnace are: the atmosphere is a mixture of oxygen and nitrogen, the oxygen volume content is 1-10%, the heating temperature is set at 200-300℃, and the heating time is 2-3 hours.

[0057] The target particles are selected from those that pass through a 20-mesh standard sieve and are retained on a 30-mesh standard sieve.

[0058] The preferred application of the adsorbent material described in this invention for adsorbing chloride ions in water is that the adsorption conditions of the adsorbent material are a pH of 4.6 to 6.8.

[0059] A method for regenerating the above-mentioned adsorbent material, wherein the regeneration method involves regenerating the material after it has adsorbed Cl... - The adsorbent material was heated, cooled, and then washed with deionized water to remove Cl from its surface. - The extracted solid is the regenerated adsorbent material.

[0060] In the above regeneration method: the heating gas atmosphere is nitrogen at a flow rate of 50-200 ml / min, the heating temperature is 150-200℃, and the heating time is 2-4 h.

[0061] Beneficial effects:

[0062] (1) Hollow glass microspheres prepared by spray laser-induced micro-explosion method have the characteristics of uniform wall thickness and high yield.

[0063] (2) The carrier of the adsorbent material is hollow glass microspheres, which ensures that the adsorbent material has sufficient mechanical strength during use.

[0064] (3) After the hollow glass microspheres of the adsorbent material are granulated by sol-gel method, preliminary pore formation is carried out using tetramethylguanidine-sodium bicarbonate pore-forming agent, and further pore formation is carried out by low-temperature plasma bombardment. This ensures that the adsorption capacity of the adsorbent material is sufficient.

[0065] (4) When the adsorbent material is bombarded by low-temperature plasma in an atmosphere containing ammonia, amino groups will form on the surface of the hollow glass microspheres. In water, the amino groups will be protonated into positively charged -NH4. + Highly efficient capture of Cl through electrostatic attraction - It can enhance the resistance to Cl - The adsorption selectivity and adsorption performance.

[0066] (5) The magnetic iron oxide nanoparticles loaded on the adsorbent material provide the advantage of easy magnetic recovery, and the magnetic iron oxide nanoparticles can effectively recover Cl. - It has a removal effect, which is especially noticeable in slightly acidic water, and it is easy to operate.

[0067] (6) The density of the adsorbent material is slightly less than that of water when it is not placed in a body of water. During the adsorption process, the density gradually increases. When the density is greater than that of water, it will sink, thus achieving the function of visualizing the adsorbent material.

[0068] (7) The magnetic iron oxide nanoparticles prepared by microemulsion coprecipitation method have the characteristics of low surface impurities, good dispersion effect and low cost.

[0069] (8) The adsorbent material has a high yield and does not require expensive materials or reagents during use, making it economically cost-effective. Attached Figure Description

[0070] Figure 1 The graphs show the adsorption effects of chloride ions in Examples 1, 2, and 3.

[0071] Figure 2 The graphs show the secondary adsorption effects of chloride ions in Examples 1, 2, and 3.

[0072] Figure 3 The graphs show the adsorption effects of chloride ions on comparative examples 1, 2, and 3.

[0073] Figure 4 The graphs show the secondary adsorption effects of chloride ions on comparative examples 1, 2, and 3. Detailed Implementation

[0074] The present invention will be further described below with reference to embodiments, but the scope of protection of the present invention is not limited thereto:

[0075] Example 1

[0076] (1) Preparation of hollow glass microsphere powder by spray laser-induced micro-explosion method

[0077] Weigh out 15g of trimethylaminoborane, 60g of silicon carbide, 12g of soda ash, 5g of limestone, and 8g of sodium fluoroborate, mix them, and melt them in a high-temperature melting furnace at 1500℃ for 2 hours to obtain 87.13g of blocky material. After cooling, place it in a centrifugal sprayer with a feed rate of 2.5L / h, a feed temperature of 400℃, an outlet temperature of 150℃, and a rotation speed of 2000rpm. After atomization by a micro centrifugal atomizer, collect the droplets with 175g of silicone oil and transfer them to a quartz carrier. The glass slide was subjected to laser irradiation at a wavelength of 355 nm, a single pulse energy of 20 μJ, and a repetition frequency of 1 kHz, along with micro-explosion induction. The droplets were cooled in an air atmosphere, placed in a beaker containing ethanol, and connected to an ultrasonic homogenizer for ultrasonic cleaning for 2 min. After hollow drying, the slide was calcined at 800 °C in a muffle furnace for 2 h, cooled, and the target product that passed through a 100-mesh standard sieve and was retained on a 500-mesh standard sieve was taken. The yield of the target product was 117.13 g.

[0078] (2) Preparation of porous hollow glass microspheres by sol-gel method

[0079] Weigh 20g of hollow glass microsphere powder obtained in step (1), add 100ml of deionized water and ultrasonically clean it three times, then mix it with 100ml of deionized water, add 6g of tetramethylguanidine-sodium bicarbonate powder (1g tetramethylguanidine, 5g sodium bicarbonate) and mix thoroughly to obtain mixed solution A;

[0080] 70g of tetraethyl orthosilicate was mixed with 10ml of 0.1mol / L NaOH aqueous solution and placed in a constant temperature heating stirrer. The mixture was stirred at 1000r / min for 1h at 25℃ to obtain mixture B. Mixture A was added to mixture B and the mixture was stirred at 175℃ for 2h. Then, ultrasonic pulse treatment was performed with a 3min operation time followed by a 1s pause and a 3s pause. The solid material was collected after filtration and allowed to stand for 2h. The target particles were screened and the target product that passed through a 20-mesh standard sieve and was retained on a 30-mesh standard sieve was obtained. The yield of the target product was 40.2g.

[0081] (3) Preparation of modified spherical particles by low-temperature plasma bombardment

[0082] The particles obtained in step (2) were transferred into an inductively coupled plasma system set to 700W, with the RF generator power set to 20W. The reaction pressure was maintained at a vacuum environment of 1.6Pa, and the bombardment time lasted for 20 minutes. Low-temperature plasma bombardment was performed in an Ar / NH3 mixed gas atmosphere (Ar volume content of 20%) at a temperature of 100℃. After bombardment, N2 was used for cooling, followed by the addition of deionized water and pulsed ultrasonic cleaning using the same method as in step (1). After drying in an oven at 60℃ for 6 hours, 40.2g of modified hollow glass microsphere spherical particles were obtained.

[0083] (4) Preparation of magnetic iron oxide nanoparticles and their loading by microemulsion coprecipitation method

[0084] Mix 10g of hexadecyltrimethylammonium bromide with 190g of cyclohexane to form solution C;

[0085] Dissolve 20g of FeCl3·6H2O in deionized water to prepare 247ml of 0.3mol / L FeCl3·6H2O aqueous solution, then quickly add 40g of polyethylene glycol 20000 to obtain solution D;

[0086] 20g of solution D was slowly added dropwise to 100g of solution C, and the mixture was stirred to obtain microemulsion A;

[0087] To prepare solution C, 320g of a 25% ammonia solution was slowly added dropwise to 100g of solution C, and the mixture was stirred to obtain microemulsion B.

[0088] 50g of microemulsion A and 60g of microemulsion B were mixed and transferred to a heated magnetic stirrer. The stirring temperature was 30℃, the speed was 1000rpm, and the stirring time was 45min. After the stirring time was completed, the mixture was transferred to a centrifuge and centrifuged at 1000rpm for 15min. The mixture was washed three times with alternating ethanol and water. After drying, the mixture was heated in a tube furnace under a weak oxidizing atmosphere (5% O2 + 95% N2) at 300℃ for 3h. After cooling, 0.13g of magnetic iron oxide nanoparticles were obtained.

[0089] Take 5g of the modified hollow glass microsphere spherical particles from step (3) and disperse them in 100ml of deionized water. Connect an ultrasonic homogenizer and ultrasonically disperse for 2min to obtain solution E.

[0090] 0.02 g of magnetic iron oxide nanoparticles were added to solution E and allowed to stand for 2 h. The product was then magnetically separated using a magnet, and the supernatant was discarded. The product was washed using a centrifuge until the washing liquid was neutral, and then dried in a tube furnace. The tube furnace drying atmosphere was set to an oxygen to nitrogen volume ratio of 5% oxygen and 95% nitrogen. The heating temperature was set to 250 °C, and the heating time was 2 h. 2.92 g of the target adsorbent material (approximately 0.1 mg per particle) was obtained by passing through a 20-mesh standard sieve and being intercepted by a 30-mesh standard sieve.

[0091] (5) Thermal desorption and regeneration of adsorbent material

[0092] Adsorbed Cl - The adsorbent material was placed in a tube furnace with a nitrogen gas inlet flow rate of 200 ml / min, a temperature of 200℃, and a heating time of 4 hours. After heating, the Cl- on the surface was washed away with deionized water. - The extracted solid is the regenerated adsorbent material.

[0093] (6) Adsorption performance test

[0094] Three sets of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid to make it acidic. The temperature was maintained at 25℃, and the adsorption was allowed to stand for 1 hour. It was found that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set to 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was detected using a CIC-D100 ion chromatograph to determine the adsorption capacity of the adsorbent material. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the adsorbent material after regeneration and desorption reached more than 90% of the first adsorption performance during the second adsorption.

[0095] Example 2

[0096] (1) Preparation of hollow glass microsphere powder by spray laser-induced micro-explosion method

[0097] 19g of trimethylaminoborane, 50g of silicon carbide, 16g of soda ash, 10g of limestone, and 5g of sodium fluoroborate were weighed and mixed. The mixture was then placed in a high-temperature melting furnace at 1400℃ for 1 hour to obtain 84.99g of lumpy material. After cooling, the material was placed in a centrifugal atomizer with a feed rate of 2L / h, a feed temperature of 300℃, an outlet temperature of 120℃, and a rotation speed of 1600rpm. After atomization by a micro-centrifugal atomizer, 170g of silicone oil was used to collect the droplets, which were then transferred to a quartz glass slide. Under the combined effects of laser irradiation at a femtosecond laser wavelength of 360 nm, single pulse energy of 15 μJ, and repetition frequency of 1.5 kHz, and micro-explosion induction, the droplet was cooled in an air atmosphere, placed in a beaker containing ethanol, connected to an ultrasonic homogenizer, ultrasonically cleaned for 2 min, dried in a hollow cavity, calcined at 600 °C for 1.5 h in a muffle furnace, cooled, and the target product that passed through a 100-mesh standard sieve and was retained on a 500-mesh standard sieve was taken. The yield of the target product was 109.99 g.

[0098] (2) Preparation of porous hollow glass microspheres by sol-gel method

[0099] Weigh 10g of hollow glass microsphere powder obtained in step (1), add 100ml of deionized water and ultrasonically clean it three times, then mix it with 100ml of deionized water, add 12g of tetramethylguanidine-sodium bicarbonate (1g tetramethylguanidine, 11g sodium bicarbonate) powder and mix thoroughly to obtain mixed solution A.

[0100] 74g of tetraethyl orthosilicate was mixed with 10ml of 0.1mol / L NaOH aqueous solution and placed in a constant temperature heating stirrer. The mixture was stirred at 30℃ for 400r / min for 0.5h to obtain mixture B. Mixture A was added to mixture B and the mixture was stirred at 150℃ for 1h. Then, ultrasonic pulse treatment was performed with a 1min operation time followed by a 2s pause. After filtration, the solid material was collected and allowed to stand for 2h. The target particles were screened and the target product that passed through a 20-mesh standard sieve and was retained on a 30-mesh standard sieve was selected. The target product was 31.35g.

[0101] (3) Preparation of modified spherical particles by low-temperature plasma bombardment

[0102] The particles obtained in step (2) were transferred into an inductively coupled plasma system with a power of 300W and an RF generator power of 20W. The reaction pressure was maintained at a vacuum environment of 0.4Pa, and the bombardment time lasted for 15 minutes. Low-temperature plasma bombardment at 150℃ was performed in an Ar / NH3 mixed gas atmosphere (Ar volume content of 16%). After bombardment, the system was cooled with N2, then deionized water was added, and the particles were cleaned using the same pulsed ultrasonic cleaning method as in step (1). The particles were then dried in an oven at 60℃ for 8 hours to obtain 31.35g of modified hollow glass microspheres.

[0103] (4) Preparation of magnetic iron oxide nanoparticles and their loading by microemulsion coprecipitation method

[0104] Mix 100g of cetyltrimethylammonium bromide with 567g of cyclohexane to form solution C;

[0105] Dissolve 20g of FeCl3·6H2O in deionized water to prepare 740ml of 0.1mol / L FeCl3·6H2O aqueous solution, then quickly add 60g of polyethylene glycol 20000 to obtain solution D;

[0106] 50g of solution D was slowly added dropwise to 100g of solution C, and the mixture was stirred to obtain microemulsion A.

[0107] To prepare solution C, 200g of a 30% ammonia solution was slowly added dropwise to 30g of solution C, and the mixture was stirred to obtain microemulsion B.

[0108] 50g of microemulsion A and 50g of microemulsion B were mixed and transferred to a heated magnetic stirrer. The stirring temperature was set at 20℃ and the speed at 800 rpm for 30 min. After stirring, the mixture was transferred to a centrifuge and centrifuged at 1600 rpm for 10 min. The mixture was washed three times with alternating ethanol and water. After drying, the mixture was heated in a tube furnace under a weak oxidizing atmosphere (5% O2 + 95% N2) at 200℃ for 2 h. After cooling, 0.11g of magnetic iron oxide nanoparticles were obtained.

[0109] Disperse 5g of modified hollow glass microspheres in step (3) in 100ml of deionized water, connect an ultrasonic homogenizer, and ultrasonically disperse for 2min to obtain solution E.

[0110] 0.01 g of magnetic iron oxide nanoparticles were added to solution E and stirred at 50 °C and 600 r / min for 0.5 h on a constant-temperature magnetic stirrer. 6.38 ml of a 0.1 mol / L NaOH aqueous solution was slowly added dropwise. After the reaction was complete, the product was magnetically separated using a magnet, and the supernatant was discarded. The product was washed with a centrifuge until the washing liquid was neutral, and then dried in a tube furnace. The tube furnace drying atmosphere was set to an oxygen to nitrogen volume ratio of 10% oxygen and 90% nitrogen, the heating temperature was set to 300 °C, and the heating time was 3 h. 2.90 g of the target adsorbent material (approximately 0.1 mg per particle) was obtained, passing through a 20-mesh standard sieve and being intercepted by a 30-mesh standard sieve.

[0111] (5) Thermal desorption and regeneration of adsorbent material

[0112] Adsorbed Cl - The adsorbent material was placed in a tube furnace with a nitrogen gas inlet flow rate of 50 ml / min, a temperature of 150℃, and a heating time of 2 hours. After heating, the Cl- on the surface was washed away with deionized water. - The extracted solid is the regenerated adsorbent material.

[0113] (6) Adsorption performance test

[0114] Three sets of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid to make it acidic. The temperature was maintained at 25℃, and the adsorption was allowed to stand for 1 hour. It was found that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set to 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was detected using a CIC-D100 ion chromatograph to determine the adsorption capacity of the adsorbent material. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the adsorbent material after regeneration and desorption reached more than 90% of the first adsorption performance during the second adsorption.

[0115] Example 3

[0116] (1) Preparation of hollow glass microsphere powder by spray laser-induced micro-explosion method

[0117] Weigh out 20g of trimethylaminoborane, 50g of silicon carbide, 12g of soda ash, 10g of limestone, and 8g of sodium fluoroborate. Mix them and melt them in a high-temperature melting furnace at 1400℃ for 2 hours to obtain 85.20g of lumpy material. After cooling, place it in a centrifugal sprayer with a feed rate of 2.5L / h, a feed temperature of 400℃, an outlet temperature of 150℃, and a rotation speed of 1600rpm. After atomization by a micro centrifugal atomizer, collect the droplets with 171g of silicone oil and transfer them to a limestone atomizer. Under the combined effects of laser irradiation (300 nm wavelength, 25 μJ single pulse, 0.5 kHz repetition rate) and micro-explosion induction, droplets on a glass slide were cooled in air, ultrasonically cleaned in an ultrasonic homogenizer connected to a beaker containing ethanol, and then hollow-dried. The resulting product was calcined at 600°C for 2 hours in a muffle furnace, cooled, and the target product, which passed through a 100-mesh standard sieve but remained on a 500-mesh standard sieve, was collected. The yield of the target product was 85.20 g.

[0118] (2) Preparation of porous hollow glass microspheres by sol-gel method

[0119] Weigh 10g of the hollow glass microsphere powder obtained in step (1), add 100ml of deionized water and ultrasonically clean it three times, then mix it with 100ml of deionized water, add 12g of tetramethylguanidine-sodium bicarbonate (2g tetramethylguanidine, 10g sodium bicarbonate) powder and mix thoroughly to obtain mixed solution A.

[0120] Take 52g of tetraethyl orthosilicate and mix it with 10ml of 0.1mol / L NaOH aqueous solution. Then, place the mixture in a constant temperature heating stirrer and stir at 30℃ for 400r / min for 1h to obtain mixture B. Add mixture A to mixture B and keep stirring at 150℃ for 2h. Then, perform ultrasonic pulse treatment with a 1min operation time followed by a 2s pause. After filtration, collect the solid material and let it stand for 2h. Then, screen the target particles and take the target product that passes through a 20-mesh standard sieve and is retained on a 30-mesh standard sieve. The target product is 25.02g.

[0121] (3) Preparation of modified spherical particles by low-temperature plasma bombardment

[0122] The particles obtained in step (2) were transferred into an inductively coupled plasma system set to 700W, with the RF generator power set to 20W. The reaction pressure was maintained at a vacuum environment of 0.4Pa, and the bombardment time lasted for 20 minutes. The particles were bombarded with low-temperature plasma at 120℃ in an Ar / NH3 mixed gas atmosphere (Ar volume content of 20%). After bombardment, the plasma was cooled with N2, then deionized water was added, and the particles were cleaned using the same pulsed ultrasonic cleaning method as in step (1). After drying in an oven at 80℃ for 8 hours, 25.01g of modified hollow glass microspheres were obtained.

[0123] (4) Preparation and loading of magnetic iron oxide nanoparticles

[0124] Mix 100g of cetyltrimethylammonium bromide with 567g of cyclohexane to form solution C;

[0125] Dissolve 20g of FeCl3·6H2O in deionized water to prepare 247ml of 0.3mol / L FeCl3·6H2O aqueous solution, then quickly add 60g of polyethylene glycol 20000 to obtain solution D;

[0126] 50g of solution D was slowly added dropwise to 100g of solution C, and the mixture was stirred to obtain microemulsion A.

[0127] To prepare solution C, 200g of a 30% ammonia solution was slowly added dropwise to 30g of solution C, and the mixture was stirred to obtain microemulsion B.

[0128] 50 ml of microemulsion A and 50 ml of microemulsion B were mixed and transferred to a heated magnetic stirrer. The stirring temperature was set at 20℃ and the speed at 800 rpm for 30 min. After stirring, the mixture was transferred to a centrifuge and centrifuged at 2000 rpm for 10 min. The mixture was washed three times with alternating ethanol and water. After drying, the mixture was heated in a tube furnace under a weak oxidizing atmosphere (5% O2 + 95% N2) at 200℃ for 2 h. After cooling, 0.27 g of magnetic iron oxide nanoparticles were obtained.

[0129] Take 5g of the modified hollow glass microspheres from step (3) and disperse them in 100ml of deionized water. After connecting to an ultrasonic homogenizer, obtain solution E.

[0130] 0.02 g of magnetic iron oxide nanoparticles were added to solution E and stirred on a constant-temperature magnetic stirrer at 50 °C and 600 r / min for 0.5 h. 17 ml of a 0.1 mol / L NaOH aqueous solution was slowly added dropwise. After the reaction was complete, the product was magnetically separated using a magnet, and the supernatant was discarded. The product was washed with a centrifuge until the washing liquid was neutral, and then dried in a tube furnace. The tube furnace drying atmosphere was set to an oxygen to nitrogen volume ratio of 10% oxygen and 90% nitrogen, the heating temperature was set to 300 °C, and the heating time was 3 h. 2.92 g of the target adsorbent material (approximately 0.1 mg per particle) was obtained, passing through a 20-mesh standard sieve and being intercepted by a 30-mesh standard sieve.

[0131] (5) Thermal desorption and regeneration of adsorbent material

[0132] Adsorbed Cl - The adsorbent material was placed in a tube furnace with a nitrogen gas inlet flow rate of 50 ml / min, a temperature of 150℃, and a heating time of 2 hours. After heating, the Cl- on the surface was washed away with deionized water. - The extracted solid is the regenerated adsorbent material.

[0133] (6) Adsorption performance test

[0134] Three sets of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid to make it acidic. The temperature was maintained at 25℃, and the adsorption was allowed to stand for 1 hour. It was found that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set to 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was detected using a CIC-D100 ion chromatograph to determine the adsorption capacity of the adsorbent material. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the adsorbent material after regeneration and desorption reached more than 90% of the first adsorption performance during the second adsorption.

[0135] Comparative Example 1

[0136] (1) Preparation of adsorption materials

[0137] Except that the adsorbent material is not subjected to low-temperature plasma bombardment, the other conditions are the same as in Example (1).

[0138] (2) Adsorption performance test

[0139] Three sets of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid to make it acidic. The temperature was maintained at 25℃, and the samples were allowed to stand for 1 hour. It was observed that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set to 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was determined using a CIC-D100 ion chromatograph to obtain the adsorption capacity of the adsorbent material. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the material after regeneration and desorption was less than 70% of the first adsorption performance.

[0140] (3) Comparison effect

[0141] Compared to Example 1, the adsorbent material adsorbs Cl without undergoing specific low-temperature plasma bombardment. - The adsorption capacity decreased significantly, and the re-adsorption effect was significantly reduced after using the desorption method in Example (1). However, it is still unknown whether the adsorption performance is due to the lack of amino loading on the surface or the decrease in specific surface area. The conclusion can be obtained through subsequent comparative example (3).

[0142] Comparative Example 2

[0143] (1) Preparation of adsorption materials

[0144] Except that the adsorbent material was not prepared and loaded with magnetic iron oxide nanoparticles, the other conditions were the same as in Example (2) for adsorption performance testing.

[0145] Three groups of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid, making it acidic. The temperature was maintained at 25℃, and the samples were allowed to stand for 1 hour. It was observed that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set at 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was measured using a CIC-D100 ion chromatograph to determine the adsorption capacity of the adsorbent material. This adsorbent material could not be recovered magnetically, and the adsorption process could not be visualized by density difference. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the material after regeneration and desorption was less than 90% of the first adsorption performance.

[0146] (3) Comparison effect

[0147] Compared to Example 2, the adsorption material, during the preparation and loading of magnetic iron oxide nanoparticles, exhibited improved Cl adsorption. - The adsorption capacity decreased significantly, and the re-adsorption effect was significantly reduced after using the desorption method in Example (1). Furthermore, without the magnetic iron oxide nanoparticles loaded, neither the magnetic recovery nor the visualization of the adsorption process was available.

[0148] Comparative Example 3

[0149] (1) Preparation of adsorption materials

[0150] Except that the gas used during the low-temperature plasma bombardment of the adsorbent material is Ar instead of NH3, the other conditions are the same as in Example (3).

[0151] (2) Adsorption performance test

[0152] Three sets of adsorbent material samples (each weighing 1g ± 0.05g) were placed in three bottles containing 100ml of 10g / L NaCl solution for adsorption. The pH of the solution was adjusted to 4.5 by adding dilute nitric acid to make it acidic. The temperature was maintained at 25℃, and the samples were allowed to stand for 1 hour. It was observed that the adsorbent material sank into the water. The mixture was then transferred to a centrifuge set to 2000rpm for 5 minutes. After filtration, the chloride ion concentration in the filtrate was detected using a CIC-D100 ion chromatograph to determine the adsorption capacity of the adsorbent material. After regeneration, the above adsorption operation was repeated. It was found that the adsorption performance of the material after regeneration and desorption was less than 90% of the first adsorption performance.

[0153] (3) Comparison effect

[0154] Compared to Example 1, the adsorbent material adsorbs Cl without undergoing specific low-temperature plasma bombardment. - The adsorption capacity decreased significantly, but compared with comparative examples (1) and (2), the adsorption performance improved again. Furthermore, after using the desorption method in example (3), the re-adsorption effect decreased significantly. It can be seen that loading amino groups onto the adsorbent material has a significant effect on the adsorption of Cl. - The performance of the adsorbent is significantly affected, but not to the point of reaching the low adsorption performance of the comparative example (1). It is concluded that the adsorbent material improves the Cl adsorption capacity during low-temperature plasma bombardment. - There are two factors that affect adsorption performance: increasing the specific surface area of ​​the adsorbent material and forming amino groups on the surface of the adsorbent material.

Claims

1. A visualizing high-efficiency removal of chloride ion adsorbent material, characterized in that: The adsorption material takes hollow glass microspheres as carriers, and the mixture of hollow glass microspheres and pore-forming agent is synthesized into hollow glass porous microspheres by sol-gel method. The surface of the porous adsorption material is modified by low-temperature plasma bombardment technology, and magnetic iron oxide nanoparticles are loaded on the porous adsorption material to prepare a chlorine ion adsorption material.

2. A method of producing the visual high-efficiency chlorine ion-removing adsorbent material according to claim 1, characterized by: The preparation method of the adsorption material is as follows: (1) Hollow glass microspheres prepared by spray laser-induced micro-explosion method The boron source, silicon source, soda ash, limestone and cosolvent are mixed and placed in a high-temperature melting furnace for melting. After cooling, a block material is obtained for atomization. After atomization, the droplets are collected with silicone oil and transferred to a quartz slide. Under the laser irradiation and micro-explosion induction of a femtosecond laser, the droplets are cooled in an air atmosphere. Finally, washing, drying and calcination are performed in sequence. After calcination and cooling, the hollow glass microspheres are obtained by sieving. (2) Preparation of porous hollow glass microsphere spherical particles by sol-gel method The hollow glass microspheres obtained in step (1) are washed and mixed with deionized water to obtain a mixed solution A. The silicon alkoxide is mixed with lye to obtain a mixed solution B. The mixed solution B is added to the mixed solution A, and then mixed and treated at 150-175°C for 1-2h. Finally, ultrasonic pulse treatment, solid material extraction by suction filtration and standing for 1-3h are performed in sequence. After standing, the porous hollow glass microsphere spherical particles are obtained by sieving. (3) Modified spherical particles prepared by low-temperature plasma bombardment The porous hollow glass microsphere spherical particles obtained in step (2) are subjected to low-temperature plasma bombardment in an Ar / NH3 mixed gas atmosphere. After bombardment, N2 is used for cooling. Then, the modified hollow glass microsphere spherical particles are obtained by washing and drying in sequence. (4) Preparation of magnetic iron oxide nanoparticles by microemulsion co-precipitation method and loading The surfactant and oil phase solvent are mixed to form solution C. The dispersing agent is added to the iron salt solution to obtain solution D. Solution D is slowly added to solution C to obtain microemulsion A. Solution C is prepared again. Ammonia solution is slowly added to solution C to obtain microemulsion B. The microemulsion A and the microemulsion B are mixed, centrifuged, washed, and dried in a tube furnace. After cooling, the magnetic iron oxide nanoparticles are obtained. The modified hollow glass microsphere spherical particles in step (3) are dispersed in deionized water to obtain solution E. The magnetic iron oxide nanoparticles are added to solution E. The magnetic stirrer is set to 50-80°C and stirred for 0.5-1h. The lye is slowly added for reaction. After the reaction is completed, the product is separated by magnet, and the supernatant is discarded. After washing to neutral, the product is dried in a tube furnace and sieved to obtain the target adsorption material.

3. The method of claim 2, wherein: The conditions of step (1) are as follows: The boron source is trimethylamine borane, the silicon source is silicon carbide, and the cosolvent is sodium fluoroborate. The mass ratio of the boron source, silicon source, soda ash, limestone and cosolvent is 15-20:50-60:10-20:5-10:1-10. The melting temperature is 1400-1500°C, and the melting time is 1-2h. The femtosecond laser has a wavelength of 300-360 nm, a single pulse energy of 15-25 μJ, and a repetition frequency of 0.5-1.5 kHz. The calcination temperature is 600-800 ℃, and the calcination time is 1.5-2 h. The target particles are screened through a 100-mesh standard sieve and retained on a 500-mesh standard sieve.

4. The method of claim 2, wherein: The conditions of step (2) are as follows: The pore-forming agent is a mixture of tetramethyl guanidine and sodium bicarbonate, and the mass ratio of tetramethyl guanidine to sodium bicarbonate is 1:(5-11). The mass ratio of the silicon alkoxide to the lye in the mixed solution B is 1:(0.1-0.3); the silicon alkoxide is tetraethyl orthosilicate, and the lye is a 0.05-0.15 mol / L sodium hydroxide solution. The mass ratio of the hollow glass microspheres, the silicon alkoxide, and the pore-forming agent powder is (10-20):(50-80):(6-15). The ultrasonic pulse treatment time is 1-3 min, and the pulse mode is 1 s of work and 2-3 s of pause. The target particles are screened through a 20-mesh standard sieve and retained on a 30-mesh standard sieve.

5. The method of claim 2, wherein: The conditions of step (3) are as follows: The low-temperature plasma bombardment conditions are as follows: the power is set to 300-700 W, the RF generator power is set to 20 W, the pressure is maintained at 0.4-1.6 Pa in a vacuum environment, the temperature is 100-150 ℃, and the bombardment time is 15-20 min. The drying temperature is 60-80 ℃, and the drying time is 6-8 h. The Ar / NH3 mixed gas contains 16-20% of Ar by volume.

6. The method of claim 2, wherein: The conditions of step (4) are as follows: The surfactant is hexadecyl trimethyl ammonium bromide, the oil phase solvent is cyclohexane, the iron salt is FeCl3·6H2O, and the dispersant is polyethylene glycol. The mass ratio of the surfactant to the oil phase solvent in the solution C is 1:(5.67-19). The concentration of the iron salt solution in the solution D is 0.1-0.3 mol / L, and the mass ratio of the iron salt to the dispersant is 1:(2-3). During the preparation of the microemulsion A, the mass of the solution C to the solution D is 1:(0.2-0.5). In the microemulsion B, the mass ratio of the solution C to the ammonia solution is 1:(1-10), and the mass concentration of the ammonia solution is 25-30%. The mass ratio of the microemulsion A to the microemulsion B is 1:(1-1.2). The conditions for heating and drying in the tube furnace are as follows: the atmosphere is a mixture of oxygen and nitrogen, the oxygen content is 1-10% by volume, the heating temperature is set to 200-300 ℃, and the heating time is 2-3 h. The conditions for drying in the tube furnace are as follows: the atmosphere is a mixture of oxygen and nitrogen, the oxygen content is 1-10% by volume, the heating temperature is set to 200-300 ℃, and the heating time is 2-3 h. The target particles are screened through a 20-mesh standard sieve and retained on a 30-mesh standard sieve.

7. The use of the adsorbent material of claim 1 for adsorbing chloride ions in water bodies.

8. Use according to claim 7, characterized in that, The adsorption conditions of the adsorbent material are as follows: the pH is 4.6-6.

8.

9. A method of regenerating the adsorbent material of claim 1, characterized by, The regeneration method is to place the adsorbent material adsorbed with Cl - under heating, and after cooling, wash the surface of Cl - with deionized water, and extract the solid to obtain the regenerated adsorbent material.

10. The regeneration method according to claim 9, characterized by: The heated gas atmosphere is 50 to 200 ml / min of nitrogen, the heating temperature is 150 to 200°C, and the heating time is 2 to 4 hours. The heated gas atmosphere is 50 to 200 ml / min of nitrogen, the heating temperature is 150 to 200°C, and the heating time is 2 to 4 hours.

Citation Information

Patent Citations

  • Preparation method of chlorine ion adsorbent

    CN105289459A